Does Temperament Underlie Infant Novel Food Responses?: Continuity of Approach–Withdrawal From 6 to 18 Months. Issue 4 (2nd August 2017) - Moding, Kameron J.; Stifter, Cynthia A.
Abstract : This study investigated whether temperamental approach–withdrawal underlies infants' responses to novel foods. Data were drawn from a longitudinal study of mother–infant dyads ( n = 136). Approach–withdrawal responses to novel foods and novel toys were coded when infants were 6 and 12 months of age. When infants were 18 months of age, approach–withdrawal behaviors, positive affect, and negative affect were used in a latent profile analysis to identify groups of toddlers who exhibited similar responses to novelty. As predicted, novel food and novel toy responses were concurrently associated at 12 months and followed a similar developmental pattern across the 1st year. Furthermore, novel food acceptance at 12 months of age, but not 6 months, predicted greater toddler approach.